Anglo-American cooperation in the Malayan Automobile market before the pacific war - Shakila Yacob (Penerbit UKM, 2011)
This article examines the relationship between American automobile multinational enterprises (MNEs) and British merchant firms in Malaya from the early twentieth century until 1942. American automobile MNEs forged a strategic relationship with British merchant firms in Malaya beginning in the early twentieth century. The “Big Three” automobile MNEs in the United States (US), namely Ford, General Motors (GM), and Chrysler formed dealership agreements with the two largest British merchant firms in Malaya – the Australian Wearne Brothers (for Ford) and the British Borneo Motors Company Ltd (for GM and Chrysler). Although Ford and GM chose to internalise their distribution in the mid-1920s in Singapore and the Dutch East Indies (DEI), respectively, the services of British merchant firms as major distributors of American automobiles in Malaya remained intact throughout the period.